2005
DOI: 10.1111/j.1532-5415.2005.53416.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Erythropoietin and Aging: A Longitudinal Analysis

Abstract: The increase in serum erythropoietin with aging may be compensation for subclinical blood loss, increased red blood cell turnover, or increased erythropoietin resistance of red cell precursors. It is suspected that, with very advanced age, or in those with compromised renal function (e.g., diabetes mellitus or hypertension), the compensatory mechanism becomes inadequate and anemia results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
86
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(93 citation statements)
references
References 24 publications
(43 reference statements)
4
86
0
3
Order By: Relevance
“…15,20,21) However, it has already been concluded that RDW predicts poor long-term outcome regardless of anemia status in AHF patients. 14,22,23) We observed that RDW was associated with low hemoglobin and depressed MCV, which are consistent with a state of impaired iron mobilization.…”
Section: Discussionmentioning
confidence: 99%
“…15,20,21) However, it has already been concluded that RDW predicts poor long-term outcome regardless of anemia status in AHF patients. 14,22,23) We observed that RDW was associated with low hemoglobin and depressed MCV, which are consistent with a state of impaired iron mobilization.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, since RDW level indicates abnormal red blood cell survival but it correlates also with the presence of severe systemic inflammatory state, undernutrition and inadequate production of EPO (3,25), this parameter has been investigated as prognostic factor and marker of disease activity in hematological malignancies [i.e., lymphocytic and myeloid leukemia, multiple myeloma, lymphoma and myelodysplastic syndrome (MDS)] (26)(27)(28)(29)(30)(31)(32)(33).…”
Section: Role Of Rdw In Hematological Tumorsmentioning
confidence: 99%
“…[18][19][20] Although some of these cases might result from myelodysplastic syndrome, Guralnik and colleagues estimated that at least one-quarter of the anemia cases in older adults would remain unexplained. 18 While erythropoietin levels have been shown to increase with aging, 8 suggesting that decreased bone marrow response or red cell survival contributes to anemia in older adults, Ferrucci and colleagues demonstrated that erythropoietin levels and pro-inflammatory cytokines were significantly lower in older Italian adults with unexplained anemia compared to non-anemic persons. 20 The genetic contribution to unexplained anemia in older adults has not been defined.…”
mentioning
confidence: 99%
“…An average decline of 0.06 g/dL per year was observed in one prospective study of adults who did not have anemia or chronic kidney disease at baseline. 8 In addition to decreasing levels with older age, variation in the distribution of hemoglobin concentration increases with age as well. To illustrate, Figure 2 shows that average hemoglobin level decreases but variance increases with each successive age group in men, although this pattern is less clear in women it did occur after the reproductive age period (>50 years).…”
mentioning
confidence: 99%